Plasma-based studies with intense X-ray and particle beam sources - Lee, R; Baldis, H; Cauble, R; Landen, O; Wark, J; Ng, A; Rose, S; Lewis, C; Riley, D; Gauthier, J; Audebert, P (2002)
The construction of short pulse (<200 fs) tunable X-ray laser sources based on the X-ray free electron laser (XFEL) concept will be a watershed for plasma-based and warm dense matter research. These new fourth generation light sources will have extremely high fields and short wavelengths (andSIM;0.1 nm) with peak spectral brightnesses 10(10) greater than third generation sources. Further, the high intensity upgrade of the GSI accelerator facilities will lead to specific energy depositions up to 200 kJ/g and temperatures between 1 and 10 eV at almost solid-state densities, enabling interesting experiments in the regime of nonideal plasmas, such as the evolution of intense ion beams in the interior of a Jovian planet. Below we discuss several applications: the creation of warm dense matter (WDM) research, probing of near solid density plasmas, and laser-plasma spectroscopy of ions in plasmas. The study of dense plasmas has been severely hampered by the fact that laser-based methods have been unavailable and these new fourth generation sources will remove these restrictions.